Influence of background suppression and retrospective realignment on free‐breathing renal perfusion measurement using pseudo‐continuous ASL. Issue 4 (25th November 2018) - Taso, Manuel; Guidon, Arnaud; Alsop, David C.
Abstract : Purpose: To assess the influence of background suppression and retrospective realignment on physiological noise and image quality in free‐breathing renal pseudo‐continuous arterial spin labeling (pCASL). Methods: Ten subjects were scanned at 3T with a pCASL prepared single‐slice coronal acquisition through the kidneys under free breathing. Multiple acquisitions were performed with various levels of residual background signal based on optimization of pulse timings to achieve specific background suppression levels (<2%, <5%, <10%, <20%). A retrospective non‐rigid motion‐correction strategy was also implemented. Results: Decreasing level of residual background signal was associated with higher temporal SNR. The retrospective motion‐correction provided an additional but not statistically significant improvement in tSNR. The highest image quality was obtained with the lowest level of residual background signal accompanied by the retrospective motion‐correction, although no significant difference in quantitative renal blood‐flow could be observed. Conclusions: Renal perfusion measurement with ASL under free breathing is feasible and robust against physiological noise when using strong background suppression strategies. Finally, retrospective motion‐correction further improves image quality but cannot replace background suppression.